Removal of impacted mandibular third molars with lingual split technique (Clinical and radiological study) - العجي, علاء; خليل, عبد الكريم (Latakia University Journal -Medical Sciences Series, 2023)
The research aims to evaluate the effectiveness of the lingual split technique for removal of impacted mandibular third molars, and to estimate the sequelae after surgery. The research sample included 20 patients who had had an impacted mandibular third molar indicated for extraction and their age under 25 years. The pain was measured by VAS scale, edema measurement relied on the Gapka and Matsumara method of measuring cheek swelling, Trismus was determined by measuring the inter-incisal distance at maximum mouth opening. Measured and evaluated have been done preoperative and on the first, third and seventh postoperative day. The results showed that the postoperative pain was at a minimum, which disappeared in 90% on the seventh day. Edema concentrated under the lower jaw and the mouth floor and reduced on the third day and disappeared on the seventh day, whilst trismus was at its upper limit in comparison with buccal approach.